A captive of wing and feather eaudiobook A retelling of swan lake. - Melanie Cellier (Beyond the Four Kingdoms, 2019)
Princess Adelaide has been missing for years. And that's exactly the way she wants it. Haunted by her past, not even the curse that entraps her is enough to make her long for her old home. But her past finds her anyway, in the form of a handsome prince from her childhood. Adelaide doesn't want to let Gabe in, but a sinister force is spreading fear throughout her new kingdom, and only Gabe has the will to help her. Adelaide can't refuse his assistance—not when the evil might soon ensnare much more than a solitary princess. But with her friends and her new kingdom in danger, even the help of Gabe and her seven swans might not be enough. In this reimagining of the classic tale, Swan Lake , the trapped princess must find the courage to overcome her past if she has any hope of turning a tragedy into a happy ending.